Late Bronze Age Copper Smelting Slags from Luserna (Trentino, Italy): Interpretation of the Metallurgical Process. (19th May 2015) - Addis, A.; Angelini, I.; Nimis, P.; Artioli, G.
Abstract : In the Late Bronze Age, the extractive metallurgy of copper in north‐eastern Italy achieved a peak of technological efficiency and mass production, as evidenced by the substantial number of metallurgical sites and the large volume of slags resulting from smelting activities. In order to define the technological features of the Late Bronze Age metallurgical process, more than 20 slags from the smelting site of Luserna (Trentino, Italy) were fully analysed by means of optical microscopy, X‐ray powder diffraction, X‐ray fluorescence spectrometry and scanning electron microscopy. Three different slag types were identified based on mineralogical and chemico‐physical parameters, each being interpreted as the product of distinct metallurgical steps. A Cu‐smelting model is proposed accordingly.